(3KbGaI GdCPf h KbGaI GdYjf (B/s - (3GdYGdj, YHO GdSdGe s; (3CdcShfOQG EcSJjQs ((3GdeZQH (B:s (3OGQ JhHbGd ddfTQ ,s, 2008)
(3GdXGgQ Gf GddZI GdYQHjI djSJ gj hMOgG GdJj JbQf GdYjf HGdJacjQ h GdGPf h GdGNdGb afbhd(B( (3UhJ GdVejQ(B) (3h (B((3Yjf GdYbd(B) (3jbGd Gf GddZGJ GdGZQjbjI h GddGJjfjI h GdLQeGfjI cdgG JQHW GdUhJ HGdVejQ h GdSeY HGdWGYI h GdGPf HGdQVhNs